To the problem of Dicrocoelium lanceatum size variability - I. D. Shelyakin; V. A. Stepanov (Российский паразитологический журнал, 2016)
Variability of Dicrocoelium lanceatum size from cattle and wild hoofed animals depending on the host, the intensity of infection and environmental conditions is studied. The greatest degree of polymorphy in D. lanceatum is expressed from farm animals.